2016
DOI: 10.1523/jneurosci.1185-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

A Basal Forebrain Site Coordinates the Modulation of Endocrine and Behavioral Stress Responses via Divergent Neural Pathways

Abstract: The bed nuclei of the stria terminalis (BST) are critically important for integrating stress-related signals between the limbic forebrain and hypothalamo-pituitary-adrenal (HPA) effector neurons in the paraventricular hypothalamus (PVH). Nevertheless, the circuitry underlying BST control over the stress axis and its role in depression-related behaviors has remained obscure. Utilizing optogenetic approaches in rats, we have identified a novel role for the anteroventral subdivision of BST in the coordinated inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 73 publications
(13 reference statements)
6
57
0
2
Order By: Relevance
“…We interpret these results as evidence for GLP1R-mediated activation of GABAergic neurons within the alBST that project to the hypothalamic PVN to put a "brake" on stress-induced activation of the HPA axis, and that GLP1R knockdown in the alBST effectively releases this brake to promote a larger, more prolonged endocrine response to stress. This interpretation is partly based on our preliminary studies using a rat ex vivo slice preparation, in which GLP1R agonists depolarized neurons within the ventral alBST that project to the PVN (Povysheva et al, 2016), and also on evidence that the projection pathway from ventral alBST to PVN is GABAergic and serves to restrain stress-induced activation of the HPA axis (Radley et al, 2009;Johnson et al, 2016). Although baseline (i.e., prestress) cort levels did not differ between GLP1R-KD and CTRL rats, it is possible that GLP1R-KD rats in our study had more pronounced cort responses to behavioral testing and day-to-day disruptions (e.g., body weight assessments), such that they experienced more total exposure to circulating cort than CTRL rats, despite their generally "less anxious" phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret these results as evidence for GLP1R-mediated activation of GABAergic neurons within the alBST that project to the hypothalamic PVN to put a "brake" on stress-induced activation of the HPA axis, and that GLP1R knockdown in the alBST effectively releases this brake to promote a larger, more prolonged endocrine response to stress. This interpretation is partly based on our preliminary studies using a rat ex vivo slice preparation, in which GLP1R agonists depolarized neurons within the ventral alBST that project to the PVN (Povysheva et al, 2016), and also on evidence that the projection pathway from ventral alBST to PVN is GABAergic and serves to restrain stress-induced activation of the HPA axis (Radley et al, 2009;Johnson et al, 2016). Although baseline (i.e., prestress) cort levels did not differ between GLP1R-KD and CTRL rats, it is possible that GLP1R-KD rats in our study had more pronounced cort responses to behavioral testing and day-to-day disruptions (e.g., body weight assessments), such that they experienced more total exposure to circulating cort than CTRL rats, despite their generally "less anxious" phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…120 Previously, Keay and Bandler had shown that besides alignment of passive coping with ventrolateral central grey, the dorsolateral column mediates active coping with escapable stressors. 120 Previously, Keay and Bandler had shown that besides alignment of passive coping with ventrolateral central grey, the dorsolateral column mediates active coping with escapable stressors.…”
Section: A Change In Environment That Necessitates a Response Activatmentioning
confidence: 99%
“…117 From there, a GABAergic network is activated that inhibits stress-induced HPA axis activity. [118][119][120] Another branch runs to the ventrolateral periaqueductal grey to execute Box 3 Role of the prefrontal cortex in top-down mediation of a stress response…”
Section: Stress Coping Circuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome is underlain by cortico-adrenal hyperactivity which is triggered by the overflow of 5-HT at hypothalamic level [19,20]. With respect to this, it is a well-known fact the ability of tianeptine to interfere with this disorder and its polysynaptic secondary effects [21 -24].…”
Section: Tianeptine and Uncoping Stress Syndromementioning
confidence: 99%